From war to change, from resistance to resilience: Vicariance, bricolage and exaptation as new metaphors to frame the post COVID-19 era - Antonio La Sala; Ryan Patrick Fuller; Mario Calabrese (Administrative Sciences, 2022)
In complex societal contexts, resilience seems the only way to survive and prosper. This is even truer when considering the present COVID-19 pandemic and its detrimental effects on global health systems and on every aspect of life. The impact was so deep that the World Health Organization (WHO) declared a global emergency on 30 January 2020. Accordingly, governments declared border closures, travel restrictions, and quarantines in the world's largest economies, also giving rise to socio-economic recessions. There is wide literature on the pandemic's impacts on people's minds and societies, yet still few studies have investigated this topic holistically, examining how language shapes both human and social sides of COVID-19's impacts. To fill this gap, this work discusses the need for new metaphorical clusters - bricolage, vicariance, and exaptation - as social sense makers to reframe a positive socially resilient response after COVID-19.
Keywords: 350; COVID-19; bricolage; exaptation; future; metaphors; resilience; vicariance